A Facile Preparation Strategy for TiO2 Spheres by Direct Hydrolysis. Issue 10 (5th August 2019) - Xin, Wuhong; Zhao, Zengdian; Yang, Xianhai; Cheng, Yingzhi; Sun, Fazhe; Feng, Liu
Abstract: We have developed a convenient and environmentally benign method for the fabrication of sub‐micron‐sized TiO2 spheres through direct hydrolysis, with the assistance of hollow detergent bubbles as template. The samples obtained at elevated temperatures are firstly characterized by X‐ray diffraction (XRD) and the corresponding photocatalytic activities are evaluated by measuring the photocatalytic oxidation of methyl orange (MO). The results reveal that relative crystallinity and crystallite size have mutual influence on photocatalytic property. Then scanning electron microscopy (SEM) and transmission electron microscopy (TEM) are carried out to investigate the morphology. It can be concluded that hollow templates transform into solid TiO2 products without auxiliary additives. This strategy is quite promising for the low cost, no waste effluent and high productivity, providing a wide range of applications in photocatalysis, catalysis, solar‐cell, separation, and purification processes. Abstract : Built on a bubble : This article reports a convenient and environmentally benign method for the fabrication of sub‐micron‐sized solid TiO2 spheres through direct hydrolysis, with the assistance of hollow detergent bubbles as template. This strategy is quite promising due to its low cost, lack of waste effluent, and high productivity.